Potential Carbon Uptake by Meranti Ecotourism Area in Balikpapan City: Implications for Emission Reduction - Muhammad Ma'arij Harfadli; Mega Ulimaz; Siti Khoriah (School of Postgraduate Studies, Diponegoro Univer, 2025)
Meranti trees can capture and store carbon from the atmosphere, helping in the mitigation of greenhouse gas emissions. The Balikpapan City government has to realize and maximize its potential. This study intends to calculate biomass, carbon stock, and CO2 uptake in the Meranti ecotourism area in Balikpapan City to help the city's emission reduction target. The biomass of meranti plants was determined using an equation. The biomass of each upper meranti plant was determined using the formula ln(AGB) = -1.533 + 2.294 x ln(DBH) + 0.56 x ln(WD). The lower part uses the equation BGB = AGB x 0.2. The analysis of carbon stocks was conducted using formula C = 0.47x (AGB+BGB). Determine the amount of carbon in leaf waste by multiplying the leaf biomass by the percentage of carbon present. The study revealed that the Meranti ecotourism area in Balikpapan City has a biomass of 7,731 g and a carbon stock of 7,092 g. Both values can decrease CO2 emissions in the atmosphere by 10,711 grams of CO2 per hectare. The Meranti ecotourism region has the potential to expedite the Balikpapan City Government's efforts to reach the aim of lowering greenhouse gas emissions.